GUGATAN ACTIO PAULIANA TERHADAP DIREKSI DAN KOMISARIS ATAS PENOLAKAN PENGEMBALIAN DIVIDEN INTERIM PEMEGANG SAHAM PERSEROAN TERBATAS - Yusuf, Chandra (Faculty of Law, Parahyangan Catholic University, 2023)
Distribution of interim dividends distributed before the end of the financial year by the Director with the approval of the Commissioner. This distribution can be made if the company's finances are in a profitable condition based on the year-end audit carried out by a Public Accountant. Companies that experience losses in their reports at the end of the year, shareholders are obliged to return interim dividends based on Law Number: 40 of 2007 concerning Limited Liability Companies. Likewise, companies experiencing bankruptcy based on Law Number: 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The curator in bankruptcy based on Auctio Pauliana with other claims can request the return of the company's interim dividends in the Commercial Court. However, the Curator can only ask for responsibility for the return of interim dividends to the Director and Commissioner jointly and severally. The obligation of the Directors, whose authority has been taken over by the Curator, is to sue the shareholders in the District Court based on Law Number: 40 of 2007 concerning Limited Liability Companies. The problem is, cases in District Court are complicated cases, not simple cases. This research uses normative juridical methods. In the discussion, the Director whose authority has been taken over by the Curator, if the shareholders reject the return of the interim dividend, will file a lawsuit in the District Court. However, a case at the District Court will take a long time, therefore the dividend return case must be submitted to the Commercial Court. In conclusion, to make it easier for the Director to file a lawsuit for the return of interim shareholder dividends in the Commercial Court, the Curator will provide a power of attorney and the case for the return of interim dividends will be made simple.